Tipping the velvet - Waters, Sarah, 1966- (Riverhead Books, 1999)
The story of a "girl-in-trousers" in 1890s England. She is a lesbian fishmonger who gains entry into the libertine world of music halls by an affair with a singer, becoming her partner in a cross-dressing show. But drama follows when the other goes straight.